Muscle temperature analysis, using thermal imaging, applied to the treatment of muscle recovery - Ovalle, Christian (2023)
The images help in the different processes where a visual interpretation of a scene is required, in this sense we find many applications where images are used to analyze, interpret and classify certain objects within the image, there are different types of images generated by different sensors, in this paper describes a method to analyze the behavior of the muscle, mainly of the knee, when performing rehabilitation exercises, coupled with an optical image where you can see the state of the muscle and the location, the method proposed as a super position between optical and thermal images, with the intention of being able to know the state of the optical image and to have the same image with information of the behavior of the temperature, the super position that we propose is to have as a base the optical image and on placing the thermal image, the results that are presented are oriented in proposing a new way of analyzing data with thermal information of the behavior of the muscles, by means of a complex image with optical and thermal information, the method is an aid in the treatment of muscular recovery, with the benefits of being scalable and applicable to other muscles and parts of the human body.